HUBUNGAN PERSEPSI PETANI TERHADAP PERAN PENYULUH PERTANIAN LAPANGAN (PPL) DENGAN TINGKAT ADOPSI INOVASI RICE TRANSPLANTER DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Riska Aprilia; Eny Lestari; Bekti Wahyu Utami (AGRITEXTS: Journal of Agricultural Extension, 2018)
This study aims to examine the role of extension workers in Kecamatan Kebakkramat. furthermore, this research is to examine the level of adoption of technological innovation  of rice transplanter and to analyze the relationship between farmers perceptions on the role of Agricultural Field Extension (PPL) with the level of adoption of rice transplanter innovation in Kecamatan Kebakkramat. The basic method of this research is quantitative descriptive method with survey technique. The location of this research is determined by purposive that is in District Kebakkramat Karanganyar Regency. Sampling was done by quota sampling with 60 respondents spread in three villages, Waru Village, Pulosari Village, and Nangsri Village, this is done because in these three villages have applied rice transplanter. The data analysis of this research using wide interval formula and rank spearman correlation analysis method (rs). The results shows that the perception of farmers on the role of extension workers as Educator (X1), Motivator (X2), Disseminator (X3), Supervisor (X4), and Facilitator (X5) in medium category or can be good. There is a significant correlation between the role of extension  agent  as  Motivator  (X2)  with  the  adoption  rate  of  rice  transplanter innovation is at 95% confidence level and the most significant correlation between extension agent role as Disseminator is at 99% (X3) level of trust. As for the role of Education (X1), Supervisor (X4), and Facilitator (X5) have no significant relationship with the adoption rate of rice transplanter innovation.